Special Issue Editors’ Notes: Linguistic diversity, equity and pedagogical innovation in higher education - Benjamin Kinsella (Universitat Autònoma de Barcelona, 2016)
This monograph will report on the results of a series of case studies conducted across several campuses of the City University of New York within a university-sponsored project entitled Futures Initiative (FI). The FI project advocates for greater equity and innovation in higher education through several actions, including research and student and teacher development initiatives. In this monograph, the authors of the contributions came together in an interdisciplinary doctoral seminar on educational language policy, which was chosen to take on an active role in the FI project. The seminar was led by Dr. Ofelia García and Dr. Carmina Makar.